Improving Students’ English Speaking Skill Through the Implementation of Talking Stick Method to the Fifth Grade Students of State Primary School 028226 Binjai - Anna Stasya Prima Sari; Ribka Kariani Br Sembiring (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
This research was primarily carried out to prove that the implementation of Talking Stick method could improve students’ English speaking skill and to describe the students’ responses to the implementation of Talking Stick method in the learning teaching processes of English speaking skill. This research is Classroom Action Research (henceforth, CAR) which was carried out in two cycles. Each cycle consisted of four meetings. The research subject of this CAR are the fifth grade students of State Primary School 028226 Binjai Class V-1 in the Academic Year of 2019/2020. There are 33 students as the research subject. The analysis of quantitative data showed that the students’ mean score increased continually from 55,63 in the pretest, 66,36 in the posttest of cycle 1, to 76,81 in the posttest of cycle 2. The analysis of qualitative data showed that the learning teaching processes of English speaking skill through the implementation of Talking Stick method ran very well. The students were more active, and motivated to learn English speaking skill. The class atmosphere was more alive and enjoyable after Talking Stick method was implemented in the English speaking classes. It is advisable that English teachers of primary school students apply Talking Stick method as one of alternatives to improve their students’ English speaking skill.